2021
DOI: 10.4102/hts.v77i4.6437
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of Ahlussunnah Waljamaah’s theology in establishing moderate Islam in Indonesia

Abstract: Radicalism and Islamic phobia have the potential to cause conflict amongst religious communities so that it needs social movements in building religious moderation. This study aims to understand and analyse the Ahlussunnah Waljamaah theology in the six largest Islamic community organisations in Indonesia in implementing religious moderation. This study uses a qualitative method with a phenomenological approach. Data obtained from interviews, observations and in-depth interviews regarding the process of externa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The study drew the conclusion that the application of religious moderation in education would be realised utilising best practice approaches by employing the grounded theory approach, which was consistent with what the prophet Muhammad exemplified in his da'wah (Muhtifah et al 2021). The Indonesian Islamic Da'wah Institute, Nahdlatul Ulama, Muhammadiyah, Rifa'iyah, Al-Irsyad and the Islamic Defenders Front were among the Islamic organisations that Kanafi et al (2021) looked at for their research on religious moderation. The six Islamic groups all adhere to Ahlussunnah wal Jama'ah's teachings, but Kanafi et al (2021) Hernawan, Riyani and Busro (2021), in his article 'Religious moderation' in the manuscript of Wawacan Babad Walangsungsang: A Sundanese religious diversity wisdom, drew the conclusion that Walangsungsang's adventure in search of understanding of interfaith knowledge was strongly packed with religious moderation.…”
Section: Introductionmentioning
confidence: 60%
“…The study drew the conclusion that the application of religious moderation in education would be realised utilising best practice approaches by employing the grounded theory approach, which was consistent with what the prophet Muhammad exemplified in his da'wah (Muhtifah et al 2021). The Indonesian Islamic Da'wah Institute, Nahdlatul Ulama, Muhammadiyah, Rifa'iyah, Al-Irsyad and the Islamic Defenders Front were among the Islamic organisations that Kanafi et al (2021) looked at for their research on religious moderation. The six Islamic groups all adhere to Ahlussunnah wal Jama'ah's teachings, but Kanafi et al (2021) Hernawan, Riyani and Busro (2021), in his article 'Religious moderation' in the manuscript of Wawacan Babad Walangsungsang: A Sundanese religious diversity wisdom, drew the conclusion that Walangsungsang's adventure in search of understanding of interfaith knowledge was strongly packed with religious moderation.…”
Section: Introductionmentioning
confidence: 60%
“…Other previous study also discus religious moderation phenomena, Syafruddin et al (2018), Zuhdi (2018), Ab Rashid et al (2020, Sirry (2020), Kanafi (2021), andSudarto (2022), This study focus on the implementation of Islamic Moderation on Islamic students in Indonesia to answer three research questions, namely; how do students define Islamic moderation? how do students perceive Islamic moderation?, What are the challenges and strategies used in implementing Islamic moderation for Islamic students in Indonesia?…”
Section: Introductionmentioning
confidence: 95%
“…There are 58.8 percent of radical sentiments among students, although 74.5% of them prefer to take moderate action (Syafruddin et al, 2018). On the other hand, Kanafi et al (2021) found that through the influence of the implementation of ahlussunah waljama' ah Islam, leaders and members of Islamic organizations in Indonesia now have a more moderate view, following the established and consistent doctrine of ahlussunah waljama' ah in various disciplines, Islamic organizations help promote the moderation character of Islam in a positive way. Ab Rashid et al (2020) Recently, Islamic Moderation in Indonesia has experienced significant opposition from various Muslim groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Religious moderation is important for maintaining the harmony of a plural life. In addition, religious moderation must be massively taught to counteract intolerance and radicalism [2]. Based on recent research, it is said that radicalism has penetrated in all walks of life.…”
Section: Introductionmentioning
confidence: 99%